Bench surgery with autotransplantation for bilateral Wilms tumor—A feasible technique for renal sinus invasion - Gao, Pengfei; Li, Jun; Chen, Huadong; Wu, Wenrui; Liu, Longshan; Jiang, Hong; Xu, Lingling; Wu, Chenglin; Fu, Qian; Liu, Juncheng; Wang, Changxi (Frontiers in Surgery, 2022)
Purpose: Bilateral Wilms tumor (BWT) with renal sinus invasion requires extremely difficult surgical care. This study presents an alternative strategy for tumor removal while at the same time preserving the renal parenchyma. Materials and methods: In total, 9 cases of synchronous BWT were admitted to our hospital between May 2016 to Aug 2020. We retrospectively reviewed the clinical data, surgical technique, and functional and oncological outcomes of these cases. Results: The 9 cases included 3 males and 6 females, with a median age of 12 months at surgery (range 7-40). A total of 14 kidney units had renal sinus invasion (77.8%), whereas multifocal neoplasms were observed in 7 units (38.9%). The local stage distribution revealed 1 kidney with stage I, 10 kidneys with stage II, and 7 kidneys with stage III. Nephron-sparing surgery was performed on 15 kidney units (83.3%), among which 13 (72.2%) underwent bench surgery with autotransplantation (BS-AT), whereas 2 (11.1%) were subjected to tumor enucleation in vivo. Urinary leakage was the most prevalent postoperative complication. We observed negative margins. During the mean follow-up of 28.4 months, 2 patients (22.2%) succumbed from sepsis and renal failure, respectively, whereas the other 7 (77.8%) survived without recurrence. Survivors experienced an estimated glomerular filtration rate of 81 ± 15.4 ml/(min×1.73m2). The endpoint renal volume of 9 renal units receiving BS-AT significantly increased (P=0.02). Conclusions: In summary, the surgical management of bilateral Wilms tumor requires meticulous operative approach and technique. Besides, BS-AT provides a viable alternative to nephron-sparing surgery for BWT patients with renal sinus invasion.